2021
DOI: 10.3390/foods10020286
|View full text |Cite
|
Sign up to set email alerts
|

Volatilome and Bioaccessible Phenolics Profiles in Lab-Scale Fermented Bee Pollen

Abstract: Bee-collected pollen (BCP) is currently receiving increasing attention as a dietary supplement for humans. In order to increase the accessibility of nutrients for intestinal absorption, several biotechnological solutions have been proposed for BCP processing, with fermentation as one of the most attractive. The present study used an integrated metabolomic approach to investigate how the use of starter cultures may affect the volatilome and the profile of bioaccessible phenolics of fermented BCP. BCP fermented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…Esters play an important role in the flavor of juice [ 37 , 38 ]. In this study, the methyl hexanoate (with an odor threshold of 87 μg/L [ 39 ]) was found to be the quantitively predominant ester compound in fermented noni juice.…”
Section: Resultsmentioning
confidence: 99%
“…Esters play an important role in the flavor of juice [ 37 , 38 ]. In this study, the methyl hexanoate (with an odor threshold of 87 μg/L [ 39 ]) was found to be the quantitively predominant ester compound in fermented noni juice.…”
Section: Resultsmentioning
confidence: 99%
“…They are efficiently utilized and a lot more affordable than previous techniques [13]. Various articles refer to fermentation using bacteria for exine dissolution such as lactic acid bacteria, Apilactobacillus kunkeei strains, and Hanseniaspora uvarum [18][19][20]. Enzymatic treatment is a valuable technique with promising results compared to fermentation as there are numerous enzymatic products commercially available at reasonable prices such as some papain, protamex TM , protease, neutral protease, cellulose, hemicellulose, or pectinase that allow the breaking of bee pollen wall down [13].…”
Section: Consumption Of Bee Pollenmentioning
confidence: 99%
“…In this regard, nectar and pollen are a source of microbes for insect pollinators as high number of bacteria exist in floral nectar (up to 10 7 CFU/mm 3 ) and pollen (10 4 -10 7 CFU/g) (Liu et al, 2019). In fact, a significant number of bacterial taxa have been identified as common to honeybee populations and flowers, including different fructophilic lactic bacteria (Liu et al, 2019;Crovadore et al, 2021) a recently discovered group of heterofermentative bacteria that prefer fructose over glucose as a carbon source (Filannino et al, 2019). Yet, pollen and nectar often contain bioactive plant secondary metabolites (Schmitt et al, 2021) as well as agrochemicals that can alter the insect microbiome composition.…”
mentioning
confidence: 99%